Clarifying species boundaries: Taxonomic revision of Aulacocheilus subrotundus (Macleay, 1825) (Coleoptera: Erotylidae) and its life cycle - Tawde, Gaurang; Pawar, Meehir; Patwardhan, Amol (Zootaxa, 2025)
In the present paper we solve the taxonomic confusion between Aulacocheilus subrotundus (Macleay, 1825) and A. quadripustulatus (Fabricius, 1801), and reinstate A. subrotundus as a distinct and valid species. Also, we describe the larvae of A. subrotundus, 2nd, 3rd and 4th stage, for the first time.